STUDI FENOMENOLOGI : PENGALAMAN KESEPIAN PADA LANSIA YANG TINGGAL DIRUMAH SEORANG DIRI DI DESA TUNGGUL WULUNG - PANDAAN - Evy Aristawati* Retty Ratnawati** Fransiska Imavike*** (The Indonesian Journal of Health Science, 2016)
Loneliness experienced on the elderly bring meaning and differentexpectations. Elderly sometimes not able to actively interact with their environmentand adapt more slowly because of the conditions they experience so thatresearchers interested in using a qualitative approach to the design ofphenomenology. The study design used is qualitative interpretativephenomenological approach . indepth interviews using semistructured questionsinvolving four elderly people who experience loneliness and in daily living at homealone. Data were collected and analyzed using thematic analysis approach basedBraun Clark. This study resulted in five themes namely the feeling of loneliness,self-assessment, emotional, situational, quality of life, the pattern of life and viewson illness and death from the seventh Where the theme converging on the mainthemes, namely the meaning of life alive. The results of the overall interviewparticipants showed one of things that support the achievement of the meaning oflife in the elderly living at home alone is a change in the spiritual aspect, in thisaspect there was an increase in integrated religion and belief in life where theelderly increasingly mature in their religious life. Spiritual terms generally expectcondition,elderly healthy physical, longevity, zest for life, remain authoritative andface death in tranquility with spiritual provisions that they have.